The genetic control of phenformin 4-hydroxylation. Issue 5 (October 1985) - Shah, R R; Evans, D A; Oates, N S; Idle, J R; Smith, R L
Abstract : Previously published results of phenformin 4-hydroxylation in 195 unrelated white British volunteers and 87 family members of 27 randomly selected probands have been subjected to genetic analysis. The results clearly show that about 9% of this population has a genetically determined defect in carrying out this oxidation reaction. The character for the defect is inherited in a Mendelian autosomal recessive fashion. The polymorphism shows a substantial degree of dominance.